1984
DOI: 10.1093/ajcn/40.6.1368
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and phosphorus intakes, balances, and blood levels of adults consuming self-selected diets

Abstract: Metabolic calcium and phosphorus balances, blood calcium and phosphorus levels, and alkaline phosphatase activity of 34 men and women, 20 to 53 yr of age, were determined each season during 1 yr while consuming customary diets. Dietary records were maintained 365 days. Analysis of variance indicated that serum Ca, P, and alkaline phosphatase levels were affected by season (p less than 0.0001), whereas calcium or phosphorus intakes were not. Calcium and phosphorus intakes of the men (1075 and 1533 mg, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A phosphorus balance of zero was observed at both levels of protein intake. Lakshmanan et al (1984) assessed calcium and phosphorus balances in 13 men aged 22-49 years and in 16 women aged 20-53 years over a 1-year period, in which subjects consumed self-selected diets. An additional three men and two women participated in the study for one-to three-quarters of the year.…”
Section: 21mentioning
confidence: 99%
“…A phosphorus balance of zero was observed at both levels of protein intake. Lakshmanan et al (1984) assessed calcium and phosphorus balances in 13 men aged 22-49 years and in 16 women aged 20-53 years over a 1-year period, in which subjects consumed self-selected diets. An additional three men and two women participated in the study for one-to three-quarters of the year.…”
Section: 21mentioning
confidence: 99%
“…The mean daily P intake of the hospital patients reported here (27.4 mmol in all twentyone patients and 29.3 mmol in balance-study patients) is similar to that reported in housebound elderly people (Bunker & Clayton, 1989), and both groups were in negative balance, though exceeding the USA recommended daily dietary allowance of 25.8 mmol (National Academy of Sciences, 1980). Although a wide range of P intakes is compatible with metabolic equilibrium some would consider the present recommendation too high (Marshall et al 1976), though negative metabolic balance has been reported in young adults consuming self-selected diets despite a high P intake (Lakshmanan et al 1984a), and a wide variation in Ca : P ratio does'not seem adversely to affect absorption and Ca status (Spencer et al 1984).…”
Section: Discussionmentioning
confidence: 70%
“…This observation illustrates why the serum calcium concentration cannot serve as a valid proxy for external calcium balance. After age 50, most adults are in slightly negative calcium balance [26] . Thus the state of calcium balance cannot be determined by simple measurement of serum calcium levels.…”
Section: Calcium Balance In Normal Adultsmentioning
confidence: 99%